Post-COVID-19 manifestations among college students: shedding the light on young adults’ health - Areej Abed Alkhormani; Reema Abdullah Alghamdi; Yara Abdulaziz Damdam; Maria Eissa Almaghrabi; Faisal F. Alamri; Muhammad Anwar Khan; Alqassem Y. Hakami (BMC Public Health)
Abstract Background Post-COVID-19 syndrome refers to a variety of symptoms that affect different organs in the body and can persist 28 days following exposure to COVID-19. Previous studies have shown that COVID-19 affects not only elderly individuals but also young adults. However, the influence of post-COVID-19 syndrome on young adults has not been studied sufficiently. Therefore, the aim of this study was to determine the prevalence and characteristics of post-COVID-19 manifestations in young adults. Methods An analytical cross-sectional online questionnaire was distributed from July 2022 to July 2023 to health sciences students in Saudi Arabia. The study used a non-probability convenience sampling technique, and the sample size was calculated to be 464. The survey included questions about the participants’ demographics, health records, COVID-19 results, duration of infection, and previous and current COVID-19 symptoms. Illness severity and management were evaluated using the COVID Experiences (COVEX) Symptoms and Diagnoses module, and Patient Health Questionnaire (PHQ-9) was used to assess depression. Results According to the inclusion criteria, 428 participants were divided into three groups: those who fully recovered within 14 days of the acute phase (76.4%), those with prolonged symptoms that resolved within 28 days (16.8%), and those with persistent symptoms for more than 28 days (6.8%). The symptom development frequency during the acute phase significantly differed among the three groups: headache (p = 0.038), loss of smell and taste (p = < 0.001), and fatigue (p = 0.009). The symptoms that significantly differed between the prolonged group and persistent group during the post-COVID-19 syndrome phase were loss of smell and taste (p = < 0.001) and shortness of breath (p = < 0.001). The study results revealed that females are susceptible to long-COVID-19. This study revealed that the overall severity of post-COVID-19 symptoms was mild in this age group. The PHQ-9 score when comparing the three groups showed a significant association with depression (p = 0.035). Conclusion The study results support the perception that not only can the geriatric population suffer from post-COVID-19 syndrome but also that young adults are prone to persistent symptoms such as loss of smell and taste, which may affect their mental health status.